Eco-Friendly Materials for Civil Construction Utilization and Advantages - Fontes Vieira, Carlos Maurício; de Castro Xavier, Gustavo; Colorado Lopera, Henry Alonso; Monteiro, Sergio Neves (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The papers published in the Special Issue "Eco-Friendly Materials for Civil Construction: Utilization and Advantages" are now collected as a reprint supporting sustainability for changing our planet lifestyle of increasing consumerist and predatory actions. Indeed, this reprint serves as a warning that the traditional linear economy entails the generation of huge amounts of wastes and, consequently, a negative impact on the environment. Therefore, emphasis on sustainable action is mandatory for the required transition from a linear to a circular economy.The collection of papers comprising this reprint are intended to contribute to advance and understanding on the role of eco-friendly construction materials. They could not only promote saving in energy but also reduce pollution by incorporating urban, agricultural, and industrial wastes.